2009
DOI: 10.1007/s00330-008-1282-5
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for virtual otoscopy in the preoperative assessment of the ossicular chain in chronic suppurative otitis media? Comparison of HRCT and virtual otoscopy with surgical findings

Abstract: The aim of this study was to assess the role of virtual otoscopy and 3D ossicular reconstruction in the preoperative assessment of the ossicles in chronic suppurative otitis media. Thirty three patients of chronic suppurative otitis media with conductive deafness (air-bone gap > 35 dB) were included in this prospective study. All patients underwent axial multidetector CT. The axial CT data set was utilized for multiplanar 2D reformations as well as virtual otoscopy (VO) and 3D reconstructions. The imaging find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…However, their protocol limited the radiologist to two standardized views with surface rendering only. Similarly, Pandey et al (2009) reported that 3D reconstructions were superior to standard 2D views for evaluation of the stapes superstructure, and results correlated strongly with intraoperative findings (Pandey et al, 2009). The radiologist in this study was limited to six standardized views.…”
Section: Discussionmentioning
confidence: 86%
“…However, their protocol limited the radiologist to two standardized views with surface rendering only. Similarly, Pandey et al (2009) reported that 3D reconstructions were superior to standard 2D views for evaluation of the stapes superstructure, and results correlated strongly with intraoperative findings (Pandey et al, 2009). The radiologist in this study was limited to six standardized views.…”
Section: Discussionmentioning
confidence: 86%
“…In his pre-operative imaging assessment of ossicles in 30 chronic suppurative otitis media with cholesteatoma patients, Pandey described that their assessments were satisfactory in larger ossicular parts. However, in the evaluation of stapes superstructure, their accuracy of MPR (in multiplanar 2D reformation) was only 76.97% [12]. In our study, it was 75% for MPR but 40% for section plane.…”
Section: Mpr Imagingmentioning
confidence: 77%
“…Pandey A.K. reported that the assessments of the larger ossicular structure tend to be satisfactory and that the accuracy of assessments of the superstructure of the stapes were 76.97% for MPR but only 40% for section plane imaging ( Pandey et al., 2009 ). This means that MPR can indicate anatomical features and pathologic conditions more precisely than section plane and can distinguish otosclerosis from absence of the ossicular chain more readily than other methods.…”
Section: Discussionmentioning
confidence: 99%